Evaluation of Paranasal Sinus Septa Types, Orientations, and Angles Using Cone Beam Computed Tomography - Kaan Orhan; Seçil Aksoy; Melis Gülbeş (Ankara University, 2023)
Purpose: This study aimed to determine the characteristics of the paranasal sinus septa and evaluate the gender differences using cone beam computed tomography (CBCT). Materials and Methods: CBCT images of 300 patients were used in this study. The number, types, and orientations of septa and the angle between the septa and the midline was measured separately on the right and left side of the maxillary, frontal and sphenoid sinuses. Coronal, axial, and sagittal sections were used for evaluations. CBCT scans were taken with Newton 3G and the images were evaluated with the NNT software program. Results: As a result of the study, it was determined that the most common type of septa in the maxillary sinus was 1 septum on one side with a rate of 28.3%. While the incidence of 1 septa on one side was the highest in the frontal sinus at 28%, and also 3 septa were found on one side with a rate of 1.3%. In the sphenoid sinus, 31% of cases with 2 septa on one side and 1 septa on the other side had the highest prevalence. There was no significant difference between men and women in terms of septa orientations and angles (p˃0.05). Conclusion: CBCT is frequently used to determine anatomical structure and variations. These results provide us with information about the anatomical characteristics and variations of the evaluated population. It is important to evaluate anatomical variations with CBCT, which provides 3-dimensional imaging using low-dose radiation, to reduce the risk of complications before surgical intervention and to perform safe sinus surgery.